An ultra-broadband perovskite-PbS quantum dot sensitized carbon nanotube photodetector. Issue 19 (2nd May 2018) - Ka, Ibrahima; Gerlein, Luis F.; Asuo, Ivy M.; Nechache, Riad; Cloutier, Sylvain G.
Abstract : A nano-engineered hybrid material consisting of SWCNTs, PbS-QDs and a halide perovskite is developed for the first time. The PbS-QDs in the hybrid system are found to be a charge generator and a charge-transfer facilitator. The hybrid material integrated into photoconductive devices shows a broad spectral response. Abstract : Organic–inorganic perovskites have been hailed as promising candidates for optoelectronic and photovoltaic devices, but their operation remains limited to the visible spectrum. Here, we combine single-wall carbon nanotubes, PbS quantum dots and a perovskite to synthesize hybrid devices suitable for operation in both the visible and near-infrared. The photodetectors thus fabricated show responsivities as high as 0.5 A W −1 and 0.35 A W −1 at 500 nm and at 1300 nm, respectively, with an applied bias of 1 V. Moreover, the incorporation of nanotubes within the perovskite matrix facilitates the carrier extraction, resulting in response time under 250 μs, a gain-bandwidth product of 0.1 MHz and detectivities of 1.4 × 10 11 Jones and 0.9 × 10 11 Jones at 500 nm and at 1300 nm, respectively. This unique approach opens new pathways for the development of low-cost, high-speed and broadband perovskite-based optoelectronic devices for large-scale manufacturing.